ANALISIS BUDAYA ORGANISASI UNTUK MENYUSUN STRATEGI ORGANISASI - Dionisius Ade Gagah Rahayaan; Yupono Bagyo; Budi Rahayu (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
This research aims to find out the organizational culture of PT. The star of Sentanu Prasodjo that is currently felt and the organizational culture that is expected. This study uses the OCAI method to see the classification of organizational culture. The variable in this study is organizational culture which is divided into four organizational cultures, namely Clan Culture, Adhocracy Culture, Market Culture, and Hierarchy Culture. The results of this study show that (1) the current perceived organizational culture is Hierarchy Culture with a value of 30.87 (2) the expected organizational culture is Market Culture with a value of 29.80.